The Effect of Self-Confidence on Students' English Speaking Ability in Front Office Subjects at State Vocational School 32 Jakarta - Destiawati, Laela; Zulfa, Vania; Marsita, Jaka (International Education Trend Issues, 2024)
This study aims to determine the influence of self-confidence on students' English speaking ability. The research method uses an associative quantitative approach and data collection in May 2024. The research was conducted by speaking English and distributing questionnaires using Google Forms. The research sample was selected using a saturated sample technique of 70 students consisting of classes XI Hospitality 1 and XI Hospitality 2. This study shows that students' self-confidence is in the medium category and students' English speaking ability is in the good category. The results of the regression test in this study showed that there was an influence of self-confidence on students' English speaking ability with a p-value of 0,002<0.05. This study shows that the higher the student's self-confidence, the better their English speaking ability and vice versa, if the student's self-confidence is low, the worse their English speaking ability will be.